2005
DOI: 10.1177/0091270005278949
|View full text |Cite
|
Sign up to set email alerts
|

Systemic and Renal Pharmacokinetics of Adefovir and Tenofovir Upon Coadministration

Abstract: Adefovir and tenofovir are nucleotide analogs that undergo renal secretion by the human renal organic anion transporter. The pharmacokinetics of tenofovir and adefovir following the administration of tenofovir disoproxil fumarate and adefovir dipivoxil alone and together were determined in 24 healthy subjects in an 8-day, open-label, fixed-sequence study. Subjects received oral doses of adefovir dipivoxil on days 1 and 8 and oral doses of tenofovir disoproxil fumarate on days 2 to 8. Pharmacokinetic sampling w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 15 publications
0
19
0
Order By: Relevance
“…Also, the maximum plasma concentration of ddI can be increased when it is administered in combination with PMPA (tenofovir) (15), thus increasing ddI-related toxicity, including pancreatitis and lactic acidosis (24). A portion of ART-treated HIV-infected individuals develop pancreatitis accompanied by increased plasma lipase and diabetes, but ART-related pancreatitis is normally lower in incidence and symptoms are milder than what was observed here (17,19).…”
Section: Resultsmentioning
confidence: 83%
See 1 more Smart Citation
“…Also, the maximum plasma concentration of ddI can be increased when it is administered in combination with PMPA (tenofovir) (15), thus increasing ddI-related toxicity, including pancreatitis and lactic acidosis (24). A portion of ART-treated HIV-infected individuals develop pancreatitis accompanied by increased plasma lipase and diabetes, but ART-related pancreatitis is normally lower in incidence and symptoms are milder than what was observed here (17,19).…”
Section: Resultsmentioning
confidence: 83%
“…ART-related toxicity can result in pancreatitis and diabetes in both humans and macaques (1,15,17,19). Previously, in studies where the same antiretroviral regimen was given to the same animal model starting at 14 weeks postinfection, we have observed an incidence of diabetes of 18% staring at 25 to 30 weeks from ART initiation (see Table S1 in the supplemental material).…”
Section: Resultsmentioning
confidence: 99%
“…The incubation concentrations of adefovir, tenofovir, and cidofovir corresponded to the therapeutic plasma levels achieved in humans (42)(43)(44). Considerable in vitro interactions between AmB-DOC and all three antiviral agents at hOAT1 were demonstrated (Fig.…”
Section: Discussionmentioning
confidence: 72%
“…Several studies have reported that HOAT-1 has a strong affinity for adefovir dipivoxil, and that individuals who show high expression levels of HOAT-1 show a higher uptake of adefovir dipivoxil in the renal proximal tubule compared with individuals who show low expression of HOAT-1 or who are deficient (37,38); this was observed in cases with tenofovir-related kidney damage (39,40). Adefovir bisphosphonate, which is the effective metabolite of adefovir dipivoxil, tends to suppress the duplication of mitochondrial DNA, leading to mitochondrial DNA loss in the renal proximal tubule, thus affecting renal tubular reabsorption and secretion (36).…”
Section: Discussionmentioning
confidence: 99%